Dialium guineense improves Lipid Profile and Oxidative Stress in Streptozotocin-induced Glycemic-impaired Diabetic Rats: Dialium guineense and metabolic indices of diabetic rats - Atanu, Francis O.; Egene, Lynda (Iranian Journal of Pharmaceutical Sciences, 2024)
In the present study, in-vivo and in-vitro approaches were utilised to investigate the antioxidant, anti-hyperglycemic and anti-hyperlipidemic activities of Ethanolic (EthEx) and Ethyl Acetate extracts (EthAcEx) of Dialium guineense (DG). In-vitro analysis of the plant extracts revealed the presence of Phenolics (43.89±0.65 and 12.16±0.27 µg/100 mg GAE for EthEx and EthAcEx respectively) and Flavonoids (3.59±0.09 and 2.56±0.39 µg/100 mg QE for EthEx and EthAcEx respectively). The in vitro antioxidant analysis revealed a DPPH IC50 of 43.45±1.14 and 108.45±0.89 µg/mL for EthEx and EthAcEx respectively. Similarly, FRAP values were EthEx 3.02±0.01 and EthAcEx 0.96±0.05 respectively. In-vitro hypoglycemic (IC50) activities were alpha-amylase: EthEx 17.15 ± 0.03 and EthAcEx 6.04±0.03 µg/mL; alpha-glucosidase EthEx 70.21±1.55 and EthAcEx 28.81±0.22 µg/mL. In-vivo analysis revealed that the plant extracts improved weight gain and alleviated glycemic impairment in Streptozotocin induced diabetic rats. In addition, the solvent extracts caused an improvement of dyslipidemia and increased the plasma activities of Superoxide Dismutase, Catalase and concentration of Glutathione. Malondialdehyde concentration was suppressed by administration of the plant extracts. Put together, the present study provides evidence for the antioxidant, anti-hyperglycemic, anti-hyperlipidemic and antidiabetic activities of DG. This suggests the potential of the plant as alternative therapy for the management of diabetes and its complications.